Carbon-ion irradiation overcomes HPV-integration/E2 gene-disruption induced radioresistance of cervical keratinocytes - Arians, Nathalie; Nicolay, Nils; Brons, Stephan; Körber, Stefan A.; Jaschke, Christine; Vercruysse, Marco; Daffinger, Sigrid; Rühle, Alexander; Debus, Jürgen; Lindel, Katja (Journal of radiation research, 2019)
Abstract. To date, only few data exist on mechanisms underlying the human papillomavirus (HPV)-associated irradiation response. It has been suggested, that the viral E2 gene plays an important role in that context. The aim of the current study is to compare the effect of photon- and carbon-ion (12C)-radiation therapy (RT) on cells with different HPV and E2 gene status. We hypothesized that 12C-RT might overcome the radioresistance of E2 gene-disrupted cells. We analyzed four different cell lines that differed in HPV status or E2 gene status. Cells were irradiated with either photons or 12C. Clonogenic survival, cell cycle and expression of Rb and p53 were analyzed. Radiosensitivity seemed to be dependent on E2 gene status and type of RT. 12C-RT led to lower surviving fractions, indicating higher radiosensitivity even in cells with disrupted E2 gene. The observed relative biological effectiveness (RBE) of 12C-RT for C33a/Caski and W12/S12 was 1.3/4 and 2.7/2.5, respectively. Cell cycle regulation after both photon- and 12C-RT was dependent on HPV status and on E2 gene status. Furthermore, the effect of RT on expression of p53 and Rb seemed to be dependent on E2 gene status and type of RT. We showed that 12C-RT overcomes HPV-integration induced radioresistance. The effect of RT on cell cycle regulation as well as on expression of p53 and Rb seemed to be dependent on HPV status, E2 gene status and type of RT. Differences in Rb expression and cell cycle regulation may play a role for enhanced radiosensitivity to 12C-RT of cells with disrupted E2 gene.